Analysis of Aflatoxin Level and Fungi Contamination From Foodstuffs Sold in Osogbo Metropolis, Nigeria - Yemisi Olukemi Adesiji; L A Bello; Adekunle Olowe; Olutoyin Catherine Adekunle; Mobolaji Omolabake Musa (University of Sultan Ageng Tirtayasa, 2025)
Some of the food products sold in open markets in Nigeria were reported to have been contaminated by Aspergillus spp that releases aflatoxin which are toxic and carcinogenic. This study sought to provide baseline information on the levels of aflatoxin in the food commodities sold in the city by determining and analyzing aflatoxin produced by isolated fungi. One hundred and ninety nine samples consisting of 67 unprocessed samples of dried maize, 66 unprocessed samples of dried groundnut and 66 unprocessed samples of dried yam chip from Igbona, Akindeko, Ayegbaju and Oluode markets in Osogbo metropolis were cultured on Potato Dextrose Agar and later sub-cultured on Aspergillus flavus parasiticus Agar with chloramphenicol (500mgL-1) supplement. Identification of isolates was carried out based on their morphological and microscopic characteristics. Aflatoxin was detected and quantified via Thin Layer Chromatography with detection limit of 1 part per billion. The highest incidence was recorded for A. flavus representing 52.4% followed by A. parasiticus (27.6%) and A. brasiliensis (20.0%). In addition, out of the nineteen food samples that yielded Aspergillus mould, 11(57.9 %) were contaminated with aflatoxins of varied concentrations ranging from 2 - ≥20 ppb, while 8 (42.1%) samples contained no aflatoxin above 1ppb. The levels of aflatoxin contamination of food products sampled were higher than set regulatory limit (≤20 ppb) in unprocessed food products by Standard Organization of Nigeria. This study's findings provided useful insights into the extent of aflatoxin contamination in the foodstuffs sold in Osogbo metropolis, Nigeria.